FINANCING OF FIXED ASSETS AS OBJECT OF STATISTICAL RESEARCH - Dmitry V. Dianov (Statistika i Èkonomika, 2016)
Statistical analysis of fixed assets as the most valuable component of national wealth is relevant not only to solve traditional problems associated with the assessment of the availability, structure and dynamics of economic assets. Fixed assets have various kinds of valuation, none of which is adequate without appropriate statistical confirmation. In particular, it concerns the investment value of fixed assets.